An Electronic Alarm device for use with Open Pan Evaporimeter (MAUSAM, 1961)
The amount of evaporation measured from open pan type evaporimeter is incorrect due to considerable amount of extraneous losses caused by birds, especially during the hot summer months in tropics, Electronic alarm device is designed to prevent the birds drinking or disturbing the water from the evaporimeter and to get reliable data of evaporation.  The comparative study of reading from two evaporimeters, one with the electronic attachment and the other without it, clearly indicates the utility of the arrangement.